Curcumin-loaded PLGA nanoparticles conjugated with anti-P-glycoprotein antibody to overcome multidrug resistance - Punfa,W. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: The encapsulation of curcumin (Cur) in polylactic-co-glycolic acid (PLGA) nanoparticles (Cur-NPs) was designed to improve its solubility and stability. Conjugation of the Cur-NPs with anti-P-glycoprotein (P-gp) antibody (Cur-NPs-APgp) may increase their targeting to P-gp, which is highly expressed in multidrugresistance (MDR) cancer cells. This study determined whether Cur-NPs-APgp could overcome MDR in a human cervical cancer model (KB-V1 cells) in vitro and in vivo. Materials and Methods: First, we determined the MDRreversing property of Cur in P-gp-overexpressing KB-V1 cells in vitro and in vivo. Cur-NPs and Cur-NPs-APgp, in the range 150-180 nm, were constructed and subjected to an in vivo pharmacokinetic study compared with Cur. The in vitro and in vivo MDR-reversing properties of Cur-NPs and Cur-NPs-APgp were then investigated. Moreover, the stability of the NPs was determined in various solutions. Results: The combined treatment of paclitaxel (PTX) with Cur dramatically decreased cell viability and tumor growth compared to PTX treatment alone. After intravenous injection, Cur-NPs-APgp and Cur-NPs could be detected in the serum up to 60 and 120 min later, respectively, whereas Cur was not detected after 30 min. Pretreatment with Cur-NPs-APgp, but not with NPs or Cur-NPs, could enhance PTX sensitivity both in vitro and in vivo. The constructed NPs remained a consistent size, proving their stability in various solutions. Conclusions: Our functional Cur-NPs-APgp may be a suitable candidate for application in a drug delivery system for overcoming drug resistance. The further development of Cur-NPs-APgp may be beneficial to cancer patients by leading to its use as either as a MDR modulator or as an anticancer drug.